Pharmacovigilance and Adverse Drug Reactions in Type 2 Diabetes Mellitus: Insights from a Tertiary Care Hospital in Central India - Rathore, Rajveer Singh; Vishwe, Akash; Kumar, Susheel; Sharma, Lokendra; Bansal, Alka; Jakhar, Punam (Scripta Medica, 2026)
Background: Type 2 Diabetes Mellitus is a chronic condition that frequently necessitates prolonged pharmacological treatment and is frequently complicated by polypharmacy and comorbid conditions. These components elevate the likelihood of adverse drug reactions that demand active pharmacovigilance to enhance drug safety and patient adherence.Methods: A prospective observational study was carried out over duration of 12 months at a tertiary care teaching hospital located in Central India. A total of 964 adults diagnosed with type 2 diabetics were enrolled. Data on demographics, comorbidities, and drug prescriptions were recorded. ADRs were identified through clinical evaluation and assessed for causality, severity, and preventability. Chi-square tests and logistic regression were utilized for statistical evaluation.Results: Among 964 patients (mean age 46.9 ± 12.4 years), the highest prevalence was observed in the 41–50 age group (32.6%). ADRs were reported in 231 patients (23.96%). Hypoglycemia (notably with sulfonylureas, p < 0.01) and gastrointestinal disturbances (mainly with metformin) were the most common ADRs. The Naranjo assessment categorized 62.3% of ADRs as probable, with 89.1% classified as mild-to-moderate in severity. According to Schumock and Thornton criteria, 54.5% of ADRs were preventable. Logistic regression revealed polypharmacy (OR = 2.73, p
Keywords: Type 2 Diabetes Mellitus, Pharmacovigilance, Adverse Drug Reactions, Naranjo Scale, Drug Safety, Polypharmacy